The Importance of International Legal Norms in Qualifying Crimes in the Field of Ecology - Utemuratova S. Sh. (Scientific Trends, 2024)
This article analyzes the significance of international legal norms in qualifying crimes in the environmental field. The influence of international conventions and agreements on national legislation, as well as their role in qualifying environmental offenses, is examined. The author emphasizes the importance of integrating international standards into national environmental legislation and highlights their role in effectively combating environmental criminality. Additionally, the article substantiates the necessity of studying international documents and aligning them with national legislation.
Keywords: Environmental crimes, international legal norms, legislation, qualification, environmental protection, international conventions, criminal liability.